Unplugged Coding in Science Learning: Strengthening Conceptual Understanding and Computational Thinking on Phase Changes of Matter among Pre Service Elementary Teachers - Rifqa Gusmida Syahrun Barokah; Neni Hermita; Mitha Dwi Anggriani; Mahmud Alpusari; Singgih Prana Putra (Universitas Pendidikan Ganesha, 2026)
Low integration of science conceptual understanding and computational thinking among pre-service elementary teachers, along with suboptimal integrated learning without reliance on digital devices. This study aims to analyze the improvement of conceptual understanding and computational thinking skills through the implementation of unplugged coding learning on the topic of changes in the state of matter. This study employed a quasi experimental design using a one-group pretest–posttest model involving thirty pre service elementary school teachers enrolled in a science education course. Data were collected through conceptual understanding tests, computational thinking performance rubrics, and classroom observation sheets, and were analyzed using descriptive statistics and normalized gain to examine improvements before and after the intervention. The results show an increase in conceptual understanding (pretest 56.8; posttest 79.4) and computational thinking skills (pretest 52.3; posttest 76.1), particularly in sequencing, conditional reasoning, and procedural representation, which indicate students’ improved ability to organize scientific processes more systematically. This study concludes that unplugged coding learning is effective in improving both conceptual understanding and computational thinking skills among pre service elementary school teachers. The implication is that this approach can serve as a practical instructional strategy to integrate science concepts and computational thinking in a coherent manner without dependence on digital devices.